Pengaruh Kapabilitas Badan Permusyawaratan Desa dan Kompetensi Aparatur Desa Terhadap Akuntabilitas Pengelolaan Dana Desa Dengan Siskeudes Sebagai Pemoderasi - Ayu Widya Puspitasari, Ida; Sujana, Edy; Putu Gede Diatmika, I (Journal of Accounting and Finance Management, 2025)
This study aims to examine the influence of the Village Consultative Body's (BPD) capability and the competence of village officials on the accountability of village fund management, with Siskeudes serving as a moderating variable. The study employs a quantitative approach using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS). The population in this study consists of all villages in Denpasar City, totaling 27 villages. The sample was selected using a non-probability sampling method, specifically purposive sampling, with 5 respondents from each village. The results indicate that the capability of the Village Consultative Body (BPD) does not significantly influence the accountability of village fund management, and the utilization of Siskeudes cannot moderate this relationship. On the other hand, the competence of village officials has a positive and significant impact on the accountability of village fund management, and the utilization of Siskeudes strengthens this relationship.